The peculiarity of the artistic conflict in the historical dramas of Zh. Tokumaeva «The Plague» and D. Mamchuyeva «Akbilek – the last star of Alanya» - Asiat M. Sarakueva (Кавказология, 2023)
The article is the first attempt in the Karachay-Balkar literary criticism to analyze the historical dramas of Zh. Tokumaeva “The Plague” and D. Mamchuyeva “Akbilek – the last star of Alanya”. This category, having arisen at the turn of the XX-XXI centuries, has not become the object of research by specialists yet. Its appearance was because of large-scale developments in society and a visible increase in interest in issues of ethnic identity and self-identification. The transition to a new evolutionary stage of national drama naturally began with an appeal to previously forbidden topics, during that time, several tragedies were created immediately devoted to deportation, religious issues, previously closed moments in the history of the Karachay-Balkarian people.Conflict institutionalizes stage literature to a much greater extent than any other genre, which determines the purpose of this article - to identify various types of conflict and conflict typology in works from the perestroika and post-perestroika periods.Several types of conflict opposition were identified during the research, using genre-typological and comparative-historical approaches: unconditional antagonism, struggle for power, clashes between feeling and duty, between “their own”, love, political, moral confrontation, and so on. It also became clear that historical drama is not limited to depicting only significant moments from an ethnic group’s heroic past, military actions - these plays are relevant and contemporary to the social, socio-political, and philosophical issues raised in them thus far. National dramatists with no experience in mastering this topic failed to complete the task set for them equally successfully (Zh. Tokumaev), but D. Mamchueva in the play “Akbilek - the last star of Alanya” overcame all the difficulties of the tragic genre and created a highly artistic work that meets the requirements of drama theory.